Mutations specifically affecting ligand interaction of the Trg chemosensory transducer. - Park, C (1986)
The Trg transducer mediates chemotactic response to galactose and ribose by interacting, respectively, with sugar-occupied galactose- and ribose-binding proteins. Adaptation is linked to methylation of specific glutamyl residues of the Trg protein. This study characterized two trg mutations that affect interaction with binding protein ligands but do not affect methylation or adaptation. The mutant phenotypes indicated that the steady-state activity of methyl-accepting sites is independent of ligand-binding activity. The mutation trg-8 changed arginine 85 to histidine, and trg-19 changed glycine 151 to aspartate. The locations of the mutational changes provided direct evidence for functioning of the amino-terminal domain of Trg in ligand recognition. Cross-inhibition of tactic sensitivity by the two Trg-linked attractants implies competition for a common site on Trg. However, the single amino acid substitution caused by trg-19 greatly reduced the response to galactose but left unperturbed the response to ribose. Thus Trg must recognize the two sugar-binding proteins at nonidentical sites, and the complementary sites on the respective binding proteins should differ. trg-8 mutants were substantially defective in the response to both galactose and ribose. An increase in cellular content of Trg-8 protein improved the response to galactose but not to ribose. It appears that Trg-8 protein is defective in the generation of the putative conformational change induced by ligand interaction. The asymmetry of the mutational defect implies that functional separation of interaction sites could persist beyond the initial stage of ligand binding.